Rhesus monkeys and baboons develop FVIII inhibitors in response to porcine endothelial cells or islets - Stewart, JM (2014)
BACKGROUND: Xenotransplantation of porcine organs holds promise of solving the human organ donor shortage. The use of α-1,3-galactosyltransferase knockout (GTKO) pig donors mitigates hyperacute rejection, while delayed rejection is currently precipitated by potent immune and hemostatic complications. Previous analysis by our laboratory suggests FVIII inhibitors might be elicited by the structurally restricted xenoantibody response which occurs after transplantation of either pig GTKO/hCD55/hCD59/hHT transgenic neonatal islet cell clusters or GTKO endothelial cells. METHODS: A recombinant xenoantibody was generated using sequences from baboons demonstrating an active xenoantibody response at day 28 after GTKO/hCD55/hCD59/hHT transgenic pig neonatal islet cell cluster transplantation. Rhesus monkeys were immunized with GTKO pig endothelial cells to stimulate an anti-nonGal xenoantibody response. Serum was collected at day 0 and 7 after immunization. A two stage chromogenic assay was used to measure FVIII cofactor activity and identify antibodies which inhibit FVIII function. Molecular modeling and molecular dynamics simulations were used to predict antibody structure and the residues which contribute to antibody-FVIII interactions. Competition ELISA was used to verify predictions at the domain structural level. RESULTS: Antibodies which inhibit recombinant human FVIII function are elicited after non-human primates are transplanted with either GTKO pig neonatal islet cell clusters or endothelial cells. There is an apparent increase of inhibitor titer by 15 Bethesda units after transplant; where an increase greater than 5 Bu can indicate pathology in humans. Furthermore, competition ELISA verifies the computer modeled prediction that the recombinant xenoantibody, H66K12, binds the C1 domain of FVIII. CONCLUSIONS: The development of FVIII inhibitors is a novel illustration of the potential impact the humoral immune response can have on coagulative dysfunction in xenotransplantation. However, the contribution of these antibodies to rejection pathology requires further evaluation because “normal” coagulation parameters after successful xenotransplantation are not fully understood.